Workers' compensation : foundations for reform - Gunderson, Morley, 1945-; Hyatt, Doug (CEL - Canadian Publishers Collection., 2000)
Topics covered include low back pain in workers' compensation, payroll taxes, unfunded liabilities, occupational health and safety, private participation, the cost, appeals litigation.